2018
DOI: 10.3892/or.2018.6222
|View full text |Cite
|
Sign up to set email alerts
|

A 60 kDa prolactin variant secreted by cervical cancer cells modulates apoptosis and cytokine production

Abstract: Abstract. Prolactin (PRL) is associated with different types of cancer, such as cervical cancer. Recombinant PRL has antiapoptotic effect on cervical cancer cells, and it can also induce cytokine production on macrophages. A 60 kDa variant of PRL is produced by cervical cancer cells. The aim of the present study was to evaluate this variant's bioactivity, to test its effect on cervical cancer cell apoptosis, and to assess its ability to induce cytokine production on THP-1 macrophages. First, 60 kDa PRL was iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…A previous study has reported that PRL has antiapoptotic effect on cervical cancer cells. 35 In our study, NRP1 was downregulated in the cervical cancer tissues compared to the normal tissues. However, a recent study has demonstrated that the expression of NRP1 was upregulated in the tumor tissues compared with the cervical intraepithelial neoplasia and normal tissues and high NRP1 expression was correlated with a poorer survival in Chinese patients with CC.…”
Section: The Prognostic Value Of This Signaturesupporting
confidence: 46%
“…A previous study has reported that PRL has antiapoptotic effect on cervical cancer cells. 35 In our study, NRP1 was downregulated in the cervical cancer tissues compared to the normal tissues. However, a recent study has demonstrated that the expression of NRP1 was upregulated in the tumor tissues compared with the cervical intraepithelial neoplasia and normal tissues and high NRP1 expression was correlated with a poorer survival in Chinese patients with CC.…”
Section: The Prognostic Value Of This Signaturesupporting
confidence: 46%
“…Our previous study discovered the presence of a PRL isoform with a molecular weight of ~60 kDa in the protein extracts and supernatants of HeLa, SiHa and C33A cells, which was absent in HaCaT cells (18). Due to the relevance that has recently been conferred to local PRL in the pathophysiology of some tumors, its bioactivity was initially determined (25). Subsequently, cells were stimulated with this PRL isoform, in order to evaluate the effects of its use separately and in combination with E2 on the mechanisms underlying cell survival and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In UCC, hPRL does not affect proliferation; however, it decreases etoposide-induced cell death; this effect is mediated by the phosphorylation of STAT3 (18,20). Recently, 60 kDa PRL, which was isolated from the supernatant of HeLa cells, was revealed to induce both responses (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variant of prolactin (PRL) is produced by cervical cancer cells. It reduced apoptosis in HeLa, SiHa and C-33A cell lines and induced IL-1β and TNF-α production by human peripheral blood mononuclear cell line THP-1 macrophages [32]. Higher doses of PRL (1000 ng/mL) induces macrophages to produce anti-inflammatory cytokine IL-10, which leads to a significant decrease in production of proinflammatory cytokines [33].…”
Section: The Molecules Involved In Forming Tamsmentioning
confidence: 99%